An evaluation of the North Sea circulation in global and regional models relevant for ecosystem simulations. (August 2017) - Pätsch, Johannes; Burchard, Hans; Dieterich, Christian; Gräwe, Ulf; Gröger, Matthias; Mathis, Moritz; Kapitza, Hartmut; Bersch, Manfred; Moll, Andreas; Pohlmann, Thomas; Su, Jian; Ho-Hagemann, Ha T.M.; et al.
Highlights: Central and northern North Sea characteristics are captured by all models. The role of the open boundaries is more important than numeric. Coastal features are resolved only by very fine grid resolution models. Different simulated transports imply different North Atlantic water penetrations. A new North Sea climatology is shown. Abstract: Simulations of the North Sea circulation by the global ocean model MPI-OM and the regional ocean models GETM, HAMSOM, NEMO, TRIM are compared against each other and with observational data for the period 1998–2009. The aim of the study is to evaluate the quality of the simulations in particular with respect to their suitability to drive biogeochemical shelf sea models. Our results demonstrate the benefit of the global model to avoid the specification of lateral open boundary conditions. Due to its stretched grid configuration, which provides a higher grid resolution at the Northwest European Shelf, the global model is able to reproduce the large-scale features, such as the water mass distribution and the thermal stratification in the central and northern North Sea, qualitatively similar to the regional models. The simulation of temperature and salinity near the coast however, shows large biases in almost all models because of the coarse meteorological forcing and too coarse vertical resolutions. The simulation of the Baltic Sea exchange and the spread of freshwater along the Norwegian coast proved difficult for all models except GETM, which reproduces impacts of the Baltic Sea outflow reasonably well.